A temperature-sensitive FERONIA mutant allele that alters root hair growth. Issue 2 (7th December 2020) - Kim, Daewon; Yang, Jiyuan; Gu, Fangwei; Park, Sungjin; Combs, Jonathon; Adams, Alexander; Mayes, Heather B; Jeon, Su Jeong; Bahk, Jeong Dong; Nielsen, Erik
Abstract: In plants, root hairs undergo a highly polarized form of cell expansion called tip-growth, in which cell wall deposition is restricted to the root hair apex. In order to identify essential cellular components that might have been missed in earlier genetic screens, we identified conditional temperature-sensitive (ts) root hair mutants by ethyl methanesulfonate mutagenesis in Arabidopsis thaliana . Here, we describe one of these mutants, feronia-temperature sensitive ( fer-ts ). Mutant fer-ts seedlings were unaffected at normal temperatures (20°C), but failed to form root hairs at elevated temperatures (30°C). Map based-cloning and whole-genome sequencing revealed that fer-ts resulted from a G41S substitution in the extracellular domain of FERONIA ( FER ). A functional fluorescent fusion of FER containing the fer-ts mutation localized to plasma membranes, but was subject to enhanced protein turnover at elevated temperatures. While tip-growth was rapidly inhibited by addition of rapid alkalinization factor 1 (RALF1) peptides in both wild-type and fer-ts mutants at normal temperatures, root elongation of fer-ts seedlings was resistant to added RALF1 peptide at elevated temperatures. Additionally, at elevated temperatures fer-ts seedlings displayed altered reactive oxygen species (ROS) accumulation upon auxin treatment and phenocopied constitutive fer mutant responses to a variety of plant hormone treatments. Molecular modeling and sequence comparison with other Catharanthus roseus receptor-like kinase 1L (CrRLK1L) receptor family members revealed that the mutated glycine in fer-ts is highly conserved, but is not located within the recently characterized RALF23 and LORELI-LIKE-GLYCOPROTEIN 2 binding domains, perhaps suggesting that fer-ts phenotypes may not be directly due to loss of binding to RALF1 peptides. Abstract : A new, temperature-sensitive allele of FERONIA rapidly inhibits FER signaling and root hair tip-growth at elevated temperatures.